EFISIENSI TEKNIS ANGGARAN BELANJA SEKTOR KESEHATAN PROPINSI JAWA BARAT - Aristyasani Putri (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2015)
The purpose of this study was to analyze the efficiency of government spending in the health sector of West Java province in improving public health as measured by indicators of health status that is Infant Mortality Rate, Mother Mortality Rate, and Life Expectancy Rate in all regencies / cities in West Java Province. DEA method used to achieve these goals. DEA works with measures to identify the units to be evaluated, the input and output of the unit. Furthermore, the calculated value of productivity and identify the unit which does not use inputs efficiently or effectively produces no output. Research indicates that although every region in the province of West Java there is an increase in the health budget annually will produce additional output (facilities and health services) are few and have not been up to meet basic health needs for the community. Budget areas that have not been efficient is because of Rp. 421.8 billion total health budget of the province of West Java is not entirely used for the procurement of facilities and health services. Only 50% of it is Rp. 213 billion to be used one of them in the provision of health facilities and servicesDOI: 10.15408/sjie.v4i2.2302